1992
DOI: 10.1111/j.1095-8649.1992.tb02645.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual status of Paralabrax humeralis (Serranidae) and infection by Philometra sp. (Nematoda: Dracunculoidea)

Abstract: Evidence is presented that Philometra sp. infects Paralabrax humeralis only after first maturity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 1 publication
3
16
0
2
Order By: Relevance
“…The negative impact of gonadinfecting philometrid nematodes on the reproductive success of their hosts has been suggested by Moravec and SalgadoMaldonado (2007), Moravec et al ( , 2008 and Perez et al (2009), among others. Oliva et al (1992) found no evidence of histological damage in the gonads of Paralabrax humeralis infected by Philometra sp., although a moderate leukocytic infiltration was detected.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The negative impact of gonadinfecting philometrid nematodes on the reproductive success of their hosts has been suggested by Moravec and SalgadoMaldonado (2007), Moravec et al ( , 2008 and Perez et al (2009), among others. Oliva et al (1992) found no evidence of histological damage in the gonads of Paralabrax humeralis infected by Philometra sp., although a moderate leukocytic infiltration was detected.…”
Section: Introductionmentioning
confidence: 85%
“…A close relationship between reproduction of the host and parasitic infection has been suggested by Oliva et al (1992). They indicated that fish that had grown larger than their size at first maturity are likely to be infected, but immature fish and hermaphrodites are not susceptible to infection.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present observations are consistent with the work of Heins and Baker (2003) who found that mean egg size in three spined stickleback (Gasterosteus aculeatus) was smaller in fish infected by the cestode, Schistocephalus solidus than in non-infected fish. Oliva et al (1992) further suggested that philometrid infection resulted in reduced fecundity in Chilean sea bass (Paralabrax humeralis) because the effective volume of the ovaries was reduced. Necrosis was described in the ovaries of striped mullet (Mugil cephalus) due to infection by Philometra cephalus (Ramachandran 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Although, many workers viz. Ramachandran (1975), Oliva et al (1992), Moravec et al (1997Moravec et al ( , 2002, Hesp et al (2002), Clarke et al (2006) and Perez et al (2009) was explored the effect of Dracunculoid nematode on the ovaries and reproductive potential in number of fish hosts. But a very little work has been done on the effect of Eustrongylides sp.…”
Section: Introductionmentioning
confidence: 99%